Latin American Culture and the Challenge of Globalization - Armony, Victor; Lamy, Paul (CIENCIA ergo-sum, 2017)
This article deals with the cultural impact of globalization on Latin American cultural. We describe the globalization processes which are bringing about profound changes in the cultural experience of Latin Americans, even in the most traditional communities. We warn that it must no be concluded too hastily the Americanized standards now tend to prevail everywhere or that local cultural patterns are disappearing or are bound to do so in the short or long term. Even though globalization increases interdependence and interconnectedness across national boundaries, we argue that these processes may give rise to a growing bybridization and heterogeneity within national and regional cultures.